THE NEW GLOBAL PUBLIC: SURVEILLANCE AND THE RISKS TO THE CIVIL SPHERE. - Dawson, Jessica (Filozofija i Drustvo, 2025)
In Douglas Adams' The Hitchhikers Guide to the Galaxy (1984), a galactic civilization built a super computer to answer the meaning of life. The answer, when given, is famously "forty-two", a once both nonsense answer and one that has taken on great cache as a marker of insider nerd knowledge. Ask a computer to define the civil sphere, it would likely be able to define the binaries of hermeneutic code but it would be unable to explain why these things are meaningful to different groups. The context would escape it. This paper argues that the meaning making that results from the binary codes of the civil sphere are not compatible with a society compressed into numbers and in fact, the binaries of computer code distort meaning making into its opposite. The global nature of the public sphere through connected communications and smart devices inverts the civil sphere into making it (i.e. repressive) by enabling surveillance by anyone anywhere in the globe and therefore removing it from local context bound together by shared beliefs. To accommodate the impact of commercial surveillance enabled data collection on the civil sphere, the theory of the civil sphere must expand to consider the consequences of data collection and ordinalization through commercial surveillance - how are the binaries of the civil sphere transformed by the binaries of life reduced to data?